2018
DOI: 10.1021/acscatal.8b02201
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Homogeneous Ethylene Dimerization Mediated by Tungsten Mono(imido) Complexes

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 73 publications
(222 reference statements)
5
34
1
Order By: Relevance
“…The tungsten bis(imido) 1-3 and mono(imido) complexes 4-5 (Scheme 1) were synthesised according to previously published procedures from our group and others. 42,43 Subsequently, complexes 1-5 were tested as pro-catalysts for the dimerisation of 1hexene after activation with EtAlCl 2 (15 equivalents) at 60 C. These test conditions are the same as those previously optimised for the dimerisation of 1-pentene using the in situ WCl 6 /ArNH 2 /Et 3 N system reported by Hanton et al 40 Our previous work has demonstrated that the nature of the imido substituent in these types of ethylene dimerisation pro-catalysts has a significant impact on the performance of the resulting catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tungsten bis(imido) 1-3 and mono(imido) complexes 4-5 (Scheme 1) were synthesised according to previously published procedures from our group and others. 42,43 Subsequently, complexes 1-5 were tested as pro-catalysts for the dimerisation of 1hexene after activation with EtAlCl 2 (15 equivalents) at 60 C. These test conditions are the same as those previously optimised for the dimerisation of 1-pentene using the in situ WCl 6 /ArNH 2 /Et 3 N system reported by Hanton et al 40 Our previous work has demonstrated that the nature of the imido substituent in these types of ethylene dimerisation pro-catalysts has a significant impact on the performance of the resulting catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, initial tests were undertaken to probe if this is also the case using 1hexene as substrate. [42][43][44]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of mono-imido derivatives, the authors isolated a polymetallic W V complex after activation of (dippN)W VI Cl 4 (THF) with MeAlCl 2 (Scheme 33). [81] Moreover, by comparison of a series of W IV , W V and W IV complexes, they assessed that W V is the most probable catalytic active species. In another study, Grubbs and Miyashita used 1,1,4,4-tetradeuterated 1,1-dilithiobutane and showed an equilibrium between nickel bis-ethylene and nickelacyclopentane complexes (Scheme 38, bottom).…”
Section: Tungstenmentioning
confidence: 99%
“…Moreover, this reaction also involves the processes of proton migration, CC bond formation, and deprotonation, which are the key steps in olefin cyclization, aromatization, and other reactions, such as methanol to olefin . Thus, in‐depth study of alkene dimerization has been done by both experimental and theoretical methods . Alkene dimerization generally proceeds with the help of catalysts.…”
Section: Introductionmentioning
confidence: 99%